2022
DOI: 10.21203/rs.3.rs-1631922/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation of the effect of silver nanoparticles alone and their combination with clarithromycin on H. pylori isolates

Abstract: Helicobacter pylori is a common bacterial pathogen responsible for gastrointestinal diseases worldwide. Clarithromycin has been considered the best tolerable and safe antibiotic in treating H. pylori infection, but increased levels of clarithromycin resistance have reduced the effectiveness of the recommended treatment regimens. So alternative treatment approaches such as nanotechnology have been considered recently. This study aimed to determine the effect of silver nanoparticles (Ag-NP) alone and their combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Growth curves provide a dynamic representation of bacterial growth over time (48 hours), whereas CFU assays provide a quantitative measure of bacterial killing, identifying the concentration at which bacterial survival is significantly reduced within only two hours of exposure time. The MIC values determined in this study are consistent with those reported for silver nanoparticles by several other research groups ( Amin et al., 2014 ; Saravanakumar et al., 2019 ; Mansouri et al., 2022 ). The action of AgNPs in the stomach is influenced by their size distribution, the formulation and to a significant extent, gastric pH.…”
Section: Discussionsupporting
confidence: 92%
“…Growth curves provide a dynamic representation of bacterial growth over time (48 hours), whereas CFU assays provide a quantitative measure of bacterial killing, identifying the concentration at which bacterial survival is significantly reduced within only two hours of exposure time. The MIC values determined in this study are consistent with those reported for silver nanoparticles by several other research groups ( Amin et al., 2014 ; Saravanakumar et al., 2019 ; Mansouri et al., 2022 ). The action of AgNPs in the stomach is influenced by their size distribution, the formulation and to a significant extent, gastric pH.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, due to the lack of an efficient strategy for eradicating H. pylori infection in the context of drug resistance, one of the focuses of research for a better therapeutic approach is on alternative and complementary methods, including AgNPs per se [ 97 ], AgNPs embedded in polymeric nanocarriers [ 98 ], or AgNPs combination with classical antibiotics [ 99 ].…”
Section: Alternative and Complementary Agnps-based Approaches In The ...mentioning
confidence: 99%
“…The results showed a small degree of growth inhibition of the bacterium compared with the studies conducted in vitro where the AgNP/clay complex showed a more obvious inhibitory effect. A study conducted in 2022 demonstrated a good efficacy of AgNPs in combination with clarithromycin compared with clarithromycin treatment only [ 99 ].…”
Section: The Antibacterial Mechanism Of Silver Nanoparticles: An Exte...mentioning
confidence: 99%
“… 64 , 73 More importantly, AgNPs have multi-target activities and interactions inside the bacterial cell which helps them escape resistance that can enhance antibacterial activities and reduce the microbial resistance when they are functionalized with macrolides. 97 , 99 The diverse mechanisms of antimicrobial action of AgNPs are summarized in Figure 4 . 3 , 81 In one study, azithromycin was functionalized with silver NPs and nanoprisms (AgNPs & AgNPrs).…”
Section: Introductionmentioning
confidence: 99%